Análisis de la resiliencia ante la vulnerabilidad sísmica de las edificaciones en la ciudad de machala - Iñiguez Siguenza, Lizbeth Michelle (2017)
Ecuador is a country with great seismic activity in which there may be the presence of telluric movements such as earthquakes or earthquakes of great intensity such as that lived in Manabí in 2016, leaving both human and material effects. Due to these events the city of Machala has to be a resilient city, in this way, would be prepared to face for any abrupt change that is manifested, as well as, to have the appropriate measures to obtain an effective and optimal recovery. Being a resilient city, the community is provided with well-being in the construction of its buildings, provided there is a professional who is capable of developing a safe design, thus achieving a sustainable development for the city. I understand resilience as the ability of any urban system to absorb and recover quickly from the impact of any tension or crisis and maintain the continuity of its services. Within the context of urban resilience, the term disaster refers to any event that is capable of causing loss of life, and implies that which can cause physical damage to people's property or urban systems, as well as disturbing in a serious or recurring manner the functionality of the same. It is for this reason that, in the present work of investigation, will be known definition of resilience, identifying when a city is resilient, in the same will be shown a curve of functionality, indicating as its name says, the operation of both structures and of its infrastructure. It will indicate the characteristics, attributes and dimensions of resilient systems, detailing each aspect in the simplest way. Once all the above mentioned information has been received, the analysis of the resilience of the city of Machala will be carried out, conducting a survey of information by means of surveys of professionals in both departments and professionals in free exercise in construction of civil works and later develop an action plan that improve the resilient capacity in it. Based on all the theoretical bases that will be exposed, a program of improvement of resilience for the city of Machala will be completed, as there are chances that natural events will hit, leaving the city affected. In order to carry out its execution, it will be necessary to redefine the analysis, design and construction processes in accordance with the established regulations, which is why it is required that both the engineers, the government and the community work together, since it would be implemented actions aimed at preventing risks, reducing negative impacts on the population and thus seeking the most favorable way to recover the city. To train the population in general on the urgent need to transform the city into safe and habitable places, through the incorporation of measures of adaptation and recovery of the impact of natural phenomena. Completed the Resilience Improvement Program, this should be imparted to others, as it has to be public knowledge so that the population knows where to turn and how to act in the face of these events.